Autoantibodies against Muscarinic Acetylcholine Receptor on Exocrine Glands in Sjögren Syndrome - Reina, Silvia Lorena (2014)
These investigations demonstrate that serum antibodies against muscarinic acetylcholine receptors (mAChR) in primary Sjögren syndrome (pSS) and associated Sjögren syndrome (aSS) bind and activate both cholinergic receptors of M3 in salivary gland and M1 in neonatal myocardium and in the cerebral frontal cortex area subtypes; triggering the production of the second messengers and proinflammatory mediators related to mAChR activation. In this way the cholinergic autoantibodies damages these receptors, which thus starts acting as an antigen. On this basis M3 and M1 mAChR IgG can be considered new markers of pSS/aSS allowing the differentiation between dry eye and mouth of autoimmune and non-autoimmune nature. Given that cholinergic autoantibodies also deregulate the parasympathetic system of the target organs, they can also be seen as a new factor contributing to the etiopathology of the syndrome.